Method for preparing biomass hard carbon material, biomass hard carbon material and application thereof

CN121449042BActive Publication Date: 2026-09-08GUANGDONG KAIJIN NEW ENERGY TECH CORP LTD
View PDF 2 Cites 0 Cited by

Patent Information

Application Number
CN202511644841.0
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2025-11-11
Publication Date
2026-09-08
Estimated Expiration
2045-11-11

AI Technical Summary

Technical Problem

(3)高温石墨化:通过极高温度处理提高材料的石墨化度,降低缺陷,但此法能耗极高且会减小层间距,反而不利于钠离子存储

Benefits of technology

[0060]为更好地说明本发明的目的、技术方案和有益效果,下面将结合具体实施例对本发明作进一步说明。需说明的是,下述实施所述方法是对本发明做的进一步解释说明,不应当作为对本发明的限制。本发明的实施例包括对生物质硬炭材料的技术方案的说明和对生物质硬炭材料的制备方法的技术方案的说明。

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN121449042B_ABST
    Figure CN121449042B_ABST
Patent Text Reader

Abstract

The application provides a preparation method of a biomass hard carbon material, the biomass hard carbon material and application thereof. The preparation method of the biomass hard carbon material comprises the following steps: drying and crushing soft biomass material to obtain a first precursor; dispersing the precursor in a mixed solution containing urea and phosphoric acid to perform reaction, and then washing and drying to obtain a second precursor; mixing the second precursor with mixed molten salt to perform ball milling to obtain a third precursor, wherein the mixed molten salt comprises AlCl3, KCl and SnCl2; performing low-temperature carbonization on the third precursor in an inert atmosphere to obtain a fourth precursor; performing high-temperature carbonization on the fourth precursor to obtain a carbide; and performing weak acid pickling on the carbide, and then washing and drying. The preparation method adopts a synergistic modification strategy combining "phosphoric acid esterification pretreatment" and "multi-component low-eutectic salt templating method", so that a biomass hard carbon material with expanded interlayer spacing and moderate graphitization degree can be prepared, and the biomass hard carbon material has high initial coulomb efficiency and good rate performance.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This invention relates to the field of new energy material preparation technology, and in particular to the preparation method of biomass hard carbon material, biomass hard carbon material and its application. Background Technology

[0002] With the rapid development of renewable energy and the dramatic increase in demand for large-scale energy storage, the development of low-cost, high-safety, and long-life rechargeable battery systems has become a research hotspot. Although lithium-ion batteries have been commercialized for many years, the scarcity and high cost of lithium resources limit their widespread application in large-scale energy storage. Sodium-ion batteries, due to their abundant resources and low cost, have become a supplementary system to lithium batteries, but sodium... + The radius (1.02 Å) is greater than that of Li. + The 0.76 Å depth results in poor sodium storage performance of traditional graphite anodes (theoretical capacity <35 mAh / g). Hard carbon materials, due to their large interlayer spacing, abundant sodium storage sites, and low cost, are considered ideal anode materials for sodium-ion batteries (SIBs). Among them, biomass hard carbon derived from agricultural waste such as bamboo shavings, bagasse, and corn cobs shows great application potential due to its wide availability, environmental friendliness, and unique natural hierarchical porous structure.

[0003] However, biomass hard carbon materials have a large specific surface area and abundant surface defect structures. During the initial charge and discharge process, the electrolyte decomposes on the material surface to form a solid electrolyte interphase (SEI) film, irreversibly consuming a large amount of sodium ions. At the same time, the abundant nanopores inside the material also irreversibly capture sodium ions. These factors together lead to a decrease in the initial coulombic efficiency of batteries using this hard carbon material, directly causing a loss in the overall battery energy density.

[0004] Secondly, the ionic radius of sodium ions (1.02 Å) is larger than that of lithium ions (0.76 Å), resulting in slow insertion and extraction kinetics in the carbon layer. Although the interlayer spacing of hard carbon (typically >0.37 nm) is larger than that of graphite (0.335 nm), the carbon layer arrangement of traditional hard carbon materials is highly disordered, the ion transport path is tortuous, and the internal resistance is large, which limits its high-rate charge and discharge performance and makes it difficult to meet the needs of fast charging applications.

[0005] To overcome the above problems, researchers have tried a variety of modification strategies, such as: (1) Precursor screening and pretreatment: Selecting specific biomass or performing pretreatments such as hydrothermal or acid washing to regulate the composition and structure of the carbon source. (2) Heteroatom doping: Introducing heteroatoms such as boron, phosphorus, sulfur, and nitrogen to expand the carbon interlayer spacing and provide more active sites. (3) High-temperature graphitization: Improving the graphitization degree of the material and reducing defects by treating it at extremely high temperatures, but this method has extremely high energy consumption and will reduce the interlayer spacing, which is not conducive to sodium ion storage. (4) Template method: Using inorganic salts (such as ZnCl2, FeCl3) or nano hard templates to create pore structures. However, existing template methods often have problems such as difficulty in removing template agents, high cost or complex processes, and it is difficult to simultaneously and accurately control the orientation arrangement of carbon layers and defect concentration. In particular, when using low-boiling-point metal chlorides such as aluminum chloride (AlCl3) as template agents / catalysts, their low boiling point (sublimation at 178℃) leads to easy volatilization and loss during carbonization, resulting in poor template effect, low catalytic efficiency, and poor reproducibility, making it difficult to achieve stable industrial production. Therefore, developing a biomass hard carbon preparation method that can simultaneously solve the two major problems of low initial efficiency and poor rate capability, and that is simple, cost-controllable, and suitable for large-scale production, is of vital importance to promoting the commercialization of sodium-ion batteries. Summary of the Invention

[0006] In view of the above problems, the purpose of this invention is to provide a method for preparing biomass hard carbon materials, the biomass hard carbon materials themselves, and their applications. The preparation method of this invention employs a synergistic modification strategy combining "phosphorylation pretreatment" and "multi-element eutectic salt template method," which can produce a biomass hard carbon material with increased interlayer spacing and moderate graphitization, exhibiting high initial coulombic efficiency and superior rate performance.

[0007] To achieve the above objectives, the first aspect of the present invention provides a method for preparing biomass hard carbon material, comprising the steps of: (I) The soft biomass material is dried and pulverized to obtain the first precursor; (II) The precursor is dispersed in a mixture containing urea and phosphoric acid, reacted, washed, and dried to obtain a second precursor; (III) The second precursor and the mixed molten salt are mixed and then ball-milled to obtain the third precursor, wherein the mixed molten salt comprises AlCl3, KCl and SnCl2; (IV) The third precursor is carbonized at low temperature under an inert atmosphere to obtain a fourth precursor, wherein the maximum temperature of the low-temperature carbonization is lower than the boiling point of the eutectic formed by the mixed molten salt. (V) The fourth precursor is subjected to high-temperature carbonization to obtain a carbide, wherein the minimum temperature of the high-temperature carbonization is higher than the boiling point of the eutectic formed by the mixed molten salt; (VI) The carbide is acid-washed with a weak acid and then dried.

[0008] The preparation method of this invention employs a synergistic modification strategy combining "phosphorylation pretreatment" and "multi-element eutectic salt template method," which can produce a biomass hard carbon material with expanded interlayer spacing and moderate graphitization degree. This material exhibits high initial coulombic efficiency and excellent rate performance, overcoming several technical bottlenecks in traditional preparation methods and providing a key material foundation for the commercialization of high-performance sodium-ion batteries. Its specific performance is as follows.

[0009] (1) Soft biomass material is selected as the precursor. β-cellulose has a high hydroxyl density, which makes it easy to react with phosphoric acid to form a stable crosslink, thus facilitating the formation of the subsequent template. Soft biomass material has a porous structure, which is conducive to the penetration of molten salt mixture to form a uniform template. Soft biomass material has a low ash content, and the removal of impurities is simpler. Weak acid can remove impurities, thus avoiding the destruction of the material structure stability by strong acid washing.

[0010] (2) In this invention, soft biomass material is first mixed with urea and phosphoric acid for reaction. During the reaction, the phosphate groups are esterified and linked to the soft biomass material molecules to modify them. The soft biomass material is pretreated by phosphoric acid esterification to introduce cross-linking sites, which lays the foundation for the subsequent stable construction of the carbon skeleton.

[0011] (3) AlCl3, KCl, and SnCl2 are selected as a mixed molten salt, and KCl is used as a flux. KCl forms a eutectic mixture with AlCl3 and SnCl2. In this liquid eutectic mixture, Al... 3+ With Sn 2+ Strong electrostatic interactions exist between ions to form a structure similar to [AlCl]. 4 ] - -[SnCl] + The ion-pair structure enhances intermolecular forces, leading to an increased boiling point in the mixture and effectively suppressing AlCl3 volatilization. During the low-temperature carbonization stage, the eutectic mixture exhibits a low-viscosity liquid state, reducing the viscosity of the molten salt system and facilitating better penetration of the molten salt into the interior of the soft biomass material. Under low-temperature carbonization, the eutectic mixture first melts to form an ionic liquid that penetrates into the phosphoric acid esterified biomass, while unvolatilized AlCl3... 3+ It readily coordinates with the -OPO3H2 groups in phosphated soft biomass materials to form [Al(HPO4)]. +The directed complex, with its octahedral configuration, exhibits strong steric hindrance, guiding the carbon layers to preferentially align along the (002) crystal plane. This reduces the full width at half maximum (FWHM) of the XRD (002) diffraction peak from approximately 5.2° to approximately 3.1°, lowering ion transport resistance and enabling precise control over the microstructure of the carbon layers. Consequently, both first-efficiency and rate performance are simultaneously improved. As temperature increases, the directed complex guides the directional dehydration and aromatization of biomass. SnCl2 acts as a reducing agent, effectively reducing the ·O2 generated during the pyrolysis of phosphate esters. - The presence of free radicals inhibits free radical side reactions and significantly reduces active defect sites in the material, thereby reducing the consumption of irreversible sodium in the formation of the SEI film in the battery. Furthermore, with increasing temperature, the residual Al / Sn component is reduced to the Al-Sn alloy phase, catalyzing the graphitization of the carbon layer. After the mixed molten salt volatilizes, the alloy template supports the formation of an extended carbon structure.

[0012] By combining "phosphorylation pretreatment" with "multi-element eutectic salt template method", hard carbon materials with a composite structure of expanded interlayer spacing and moderate graphitization can be prepared. The large interlayer spacing is conducive to the rapid insertion / extraction of sodium ions, resulting in better fast charging performance, while the moderate graphitization and reduced defect density together ensure high first coulombic efficiency.

[0013] In some embodiments, the soft biomass material is selected from at least one of bamboo shavings, bagasse, corn cobs, and corn stalks.

[0014] In some implementations, the soft biomass material is vacuum dried to remove free water and then subjected to airflow pulverization to obtain the first precursor. The vacuum drying temperature is 50~75℃ and the time is 5~20h. In some implementations, the Dv50 of the first precursor is 1~10 μm.

[0015] In some embodiments, the molar ratio of urea to phosphoric acid is 1:2 to 5.

[0016] In some embodiments, the concentration of phosphoric acid is 85 wt.% or higher.

[0017] In some embodiments, boric acid is also added to the mixture, wherein the boric acid accounts for 3 to 10 wt.% of the mixture.

[0018] In some embodiments, the reaction is carried out at a temperature of 120-200°C for a time of 1-6 hours.

[0019] In some embodiments, the solid-liquid ratio of the first precursor and the mixture is 1:10~20 g / mL.

[0020] In some embodiments, the washing in step (II) is a centrifugal washing with water until the pH is 6.5±0.2, and the drying is a vacuum drying at 70~100°C for 6~20h.

[0021] In some embodiments, the weight ratio of AlCl3 to KCl is 1:3 / 7 to 7 / 3, and SnCl2 accounts for 10 to 20% of the sum of the weights of AlCl3 and KCl.

[0022] In some embodiments, the weight ratio of the second precursor to the mixed molten salt is 1:1 to 2.

[0023] In some embodiments, the ball mill rotates at a speed of 200-400 rpm for a time of 2-10 hours.

[0024] In some embodiments, the inert atmosphere is selected from at least one of argon, nitrogen, helium, neon, krypton, and xenon.

[0025] In some embodiments, the boiling point of the eutectic formed by the mixed molten salt is 300~500°C.

[0026] In some embodiments, the high-temperature carbonization includes raising the temperature to 1100-1400°C at a rate of 3-8°C / min and holding it for 1-5 hours.

[0027] In some implementations, the pickling time is 3 to 15 hours and the temperature is 60 to 100°C.

[0028] In some embodiments, the washing in step (VI) includes washing with water until the pH is 6.0 ± 0.2, and the drying is vacuum drying at 70-100°C for 6-20 hours.

[0029] In some embodiments, the degree of substitution (DP) of the phosphate group in the second precursor is 0.2 to 0.4.

[0030] In some implementations, the low-temperature carbonization employs a multi-stage carbonization process, with the highest temperature of the low-temperature carbonization being below 500°C.

[0031] In some embodiments, the multi-stage carbonization includes raising the temperature to 200-280°C at a rate of 1-10°C / min and holding for 0.5-3.0 h, and then raising the temperature to 300-500°C at a rate of 0.5-5.0°C / min and holding for 1-5 h.

[0032] In some implementations, the weak acid is acetic acid.

[0033] In some embodiments, the solid-liquid ratio of the carbide to the weak acid is 1:15~25 g / mL, and the concentration of the acetic acid is 0.5~2.0 mol / L.

[0034] The second aspect of the present invention provides a biomass hard carbon material prepared by the aforementioned method for preparing biomass hard carbon material, wherein the d002 is 0.39~0.42nm, the degree of graphitization ID / IG is 0.90~1.10, and the full width at half maximum (FWHM) of the XRD 002 diffraction peak is 3.1±0.4°.

[0035] In some implementations, nitrogen and phosphorus are doped, with nitrogen doping amounting to 0.8 to 1.3 wt.% and phosphorus doping amounting to 1.0 to 1.8 wt.%.

[0036] In some implementations, the 0.1C first reversible capacity is ≥335mAh / g.

[0037] In some implementations, the coulombic efficiency of the first charge-discharge cycle at 0.1C is ≥82.8%.

[0038] In some implementations, the 5C capacity is ≥255mAh / g.

[0039] In some implementations, the 5C capacity retention rate is ≥75%. Attached Figure Description

[0040] Figure 1 The TG test results are for the mixed molten salt in step (III) of Example 1 and Comparative Example 1.

[0041] Figure 2 EPR detection signal diagrams for the fourth precursors of Example 1 and Comparative Example 1. Detailed Implementation

[0042] The biomass hard carbon material of this invention can be used alone or in combination with other negative electrode active materials (such as natural graphite, silicon oxide materials, silicon carbon materials, soft carbon, and / or hard carbon). The biomass hard carbon material can be applied in secondary batteries, which include positive electrode active materials and negative electrode active materials. Positive electrode active materials include layered oxide series sodium-ion positive electrode materials, Prussian blue (white) series sodium-ion positive electrode materials, and polyanionic compound series sodium-ion positive electrode materials.

[0043] The biomass hard carbon material of this invention, when used as a negative electrode material in sodium-ion batteries, exhibits an initial reversible capacity of ≥335 mAh / g at 0.1C. Examples, but not limited to, 335 mAh / g, 340 mAh / g, 345 mAh / g, 350 mAh / g, 355 mAh / g, 360 mAh / g, 365 mAh / g, 370 mAh / g, 375 mAh / g, 380 mAh / g, 385 mAh / g, 390 mAh / g, 395 mAh / g, and 400 mAh / g. The initial coulombic efficiency at 0.1C is ≥82.8%, examples, but not limited to, 82.8%, 83.0%, 83.5%, 84.0%, 84.5%, 85.0%, 85.5%, 86.0%, 86.5%, 87.0%, 87.5%, 88.0%, 88.5%, 89.0%, 89.5%, and 90.0%. 5C capacity ≥ 255mAh / g, for example, but not limited to 255mAh / g, 260mAh / g, 265mAh / g, 270mAh / g, 275mAh / g, 280mAh / g, 285mAh / g, 290mAh / g, 295mAh / g, 300mAh / g. 5C capacity retention ≥ 75%, for example, but not limited to 75%, 76%, 77%, 78%, 79%, 80%, 81%, 82%, 83%, 84%, 85%.

[0044] The d002 of the biomass hard carbon material is 0.39–0.42 nm, which is higher than the conventional 0.36–0.38. For example, d002 can be, but is not limited to, 0.39 nm, 0.40 nm, 0.41 nm, and 0.42 nm. The graphitization degree ID / IG is 0.90–1.10, and for example, ID / IG can be, but is not limited to, 0.90, 0.92, 0.94, 0.96, 0.98, 1.00, 1.02, 1.04, 1.06, 1.08, and 1.10. The XRD 002 diffraction peak full width at half maximum (FWHM) is 3.1 ± 0.4°, lower than the conventional 5.2 ± 0.2°. The material has a higher d002, a smaller XRD 002 diffraction peak FWHM, and a graphitization degree ID / IG close to 1, thus resulting in better first coulombic efficiency and rate performance. The biomass hard carbon material of the present invention is doped with nitrogen and phosphorus. The nitrogen doping amount is 0.8~1.3 wt.%, and as examples, but not limited to, 0.8 wt.%, 0.9 wt.%, 1.0 wt.%, 1.1 wt.%, 1.2 wt.%, and 1.3 wt.%. The phosphorus doping amount is 1.0~1.8 wt.%, and as examples, but not limited to, 1.0 wt.%, 1.1 wt.%, 1.2 wt.%, 1.3 wt.%, 1.4 wt.%, 1.5 wt.%, 1.6 wt.%, 1.7 wt.%, and 1.8 wt.%.

[0045] The preparation method of the biomass hard carbon material of the present invention may include the following steps.

[0046] (I) The soft biomass material is dried and pulverized to obtain the first precursor.

[0047] (II) The precursor is dispersed in a mixture containing urea and phosphoric acid, reacted, washed and dried to obtain the second precursor.

[0048] (III) The third precursor is obtained by ball milling the second precursor and the mixed molten salt.

[0049] (IV) The third precursor was carbonized at low temperature under an inert atmosphere to obtain the fourth precursor.

[0050] (V) The fourth precursor is carbonized at high temperature to obtain a carbide. The minimum temperature of high-temperature carbonization is higher than the boiling point of the eutectic formed by the mixed molten salt.

[0051] (VI) The carbides are acid-washed with a weak acid, then washed and dried.

[0052] In step (I), the soft biomass material is selected from at least one of bamboo shavings, sugarcane bagasse, corn cobs, and corn stalks. For example, the soft biomass material is selected from sugarcane bagasse. Sugarcane bagasse is dominated by cellulose and hemicellulose, with a composition of 15 wt.% lignin, 55 wt.% cellulose, and 30 wt.% hemicellulose. It has very low ash content, and most impurities can be removed with mild acetic acid. The soft biomass material is vacuum dried to remove free water, and then subjected to air-jet milling to obtain the first precursor. The vacuum drying temperature is 50~75℃. For example, the temperature can be, but is not limited to, 50℃, 55℃, 60℃, 65℃, 70℃, and 75℃. The drying time is 5~20h. For example, the time can be, but is not limited to, 5h, 6h, 7h, 8h, 9h, 10h, 11h, 12h, 13h, 14h, 15h, 16h, 17h, 18h, 19h, and 20h. The Dv50 of the first precursor is 1~10μm. For example, Dv50 can be, but is not limited to, 1μm, 2μm, 3μm, 4μm, 5μm, 6μm, 7μm, 8μm, 9μm, or 10μm.

[0053] In step (II), the molar ratio of urea to phosphoric acid is 1:2 to 5. For example, the molar ratio may be, but is not limited to, 1:2, 1:3, 1:4, or 1:5. The concentration of phosphoric acid is 85 wt.% or higher. For example, it may be, but is not limited to, 85 wt.%, 86 wt.%, 87 wt.%, 88 wt.%, 89 wt.%, or 90 wt.%. Furthermore, boric acid may be added to the mixture, accounting for 3 to 10 wt.% of the mixture. For example, it may be, but is not limited to, 3 wt.%, 4 wt.%, 5 wt.%, 6 wt.%, 7 wt.%, 8 wt.%, 9 wt.%, or 10 wt.%. Adding boric acid acts as a stabilizer to inhibit biuret formation and improve reaction uniformity. The reaction temperature is 120~200℃. For example, the temperature can be, but is not limited to, 120℃, 130℃, 140℃, 150℃, 160℃, 170℃, 180℃, 190℃, or 200℃. The reaction time is 1~6 hours. For example, the time can be, but is not limited to, 1 hour, 2 hours, 3 hours, 4 hours, 5 hours, or 6 hours. The solid-liquid ratio of the first precursor to the mixed solution is 1:10~20 g / mL. For example, the solid-liquid ratio can be, but is not limited to, 1:10 g / mL, 1:11 g / mL, 1:12 g / mL, 1:13 g / mL, 1:14 g / mL, 1:15 g / mL, 1:16 g / mL, 1:17 g / mL, 1:18 g / mL, 1:19 g / mL, or 1:20 g / mL. In this step, washing is performed using a centrifuge until the pH reaches 6.5 ± 0.2, and drying is performed under vacuum at 70–100°C for 6–20 hours. For example, the temperature can be, but is not limited to, 70°C, 75°C, 80°C, 85°C, 90°C, 95°C, or 100°C, and the time can be, but is not limited to, 6 hours, 8 hours, 10 hours, 12 hours, 14 hours, 16 hours, 18 hours, or 20 hours. The degree of substitution (DP) of the phosphate group in the second precursor is 0.2–0.4. For example, the degree of substitution (DP) can be, but is not limited to, 0.2, 0.3, or 0.4.

[0054] The formula for calculating the degree of substitution is as follows. Where, C p The value is the phosphorus concentration (μg / mL) measured by ICP, V is the volume of the test (mL), msample is the mass (g) of the second precursor, and %ptheoretical is the theoretical phosphorus content when fully substituted (calculated based on the theoretical phosphorus content of 11.8% for complete phosphorylation of cellulose glucose unit (C6H10O5).

[0055]

[0056] In step (III), the mixed molten salt comprises AlCl3, KCl, and SnCl2. The weight ratio of AlCl3 to KCl is 1:3 / 7 to 7:3, and examples, but not limited to, are 1:3 / 7, 1:1, 1:2, 2:1, 2:3, 3:2, 3:4, 3:5, 4:3, 4:5, 4:7, 5:3, 5:4, 5:6, 5:7, 5:8, 5:9, 6:5, 6:7, 6:11, 7:4, 7:5, and 1:7 / 3. SnCl2 accounts for 10 to 20% of the total weight of AlCl3 and KCl, and examples, but not limited to, are 10%, 12%, 14%, 16%, 18%, and 20%. The boiling point of the eutectic formed by the mixed molten salt is 300~500℃, and for example, but not limited to, 300℃, 320℃, 340℃, 360℃, 380℃, 400℃, 420℃, 440℃, 460℃, 480℃, and 500℃. The weight ratio of the second precursor to the mixed molten salt is 1:1~2, and for example, but not limited to, 1:1 or 1:2. The ball milling speed is 200~400 rpm, and for example, but not limited to, 200 rpm, 220 rpm, 240 rpm, 260 rpm, 280 rpm, 300 rpm, 320 rpm, 340 rpm, 360 rpm, 380 rpm, and 400 rpm. The milling time is 2~10h, and for example, but not limited to, 2h, 3h, 4h, 5h, 6h, 7h, 8h, 9h, and 10h.

[0057] In step (IV), the highest temperature of the low-temperature carbonization is lower than the boiling point of the eutectic formed by the mixed molten salt, thus suppressing the volatilization of AlCl3. The inert atmosphere is selected from at least one of argon, nitrogen, helium, neon, krypton, and xenon. During low-temperature carbonization, SnCl2 has reducing properties and can effectively reduce the ·O2 generated during the pyrolysis of phosphate esters. -Free radicals are present, thus weakening the EPR detection signal. Low-temperature carbonization employs a multi-stage carbonization process, with the highest temperature below 500℃. Multi-stage carbonization involves heating to 200-280℃ at a rate of 1-10℃ / min and holding for 0.5-3.0h, followed by heating to 300-500℃ at a rate of 0.5-5.0℃ / min and holding for 1-5h. Through multi-stage carbonization, at low temperatures, AlCl3-SnCl2-KCl melts to form an ionic liquid, which penetrates into the phosphorylated biomass to form directed complexes. In the intermediate temperature stage, the directed complexes guide the directional dehydration and aromatization of the biomass, with SnCl2 acting as a reducing agent to suppress free radical side reactions. Multi-stage carbonization can be two-stage, two-stage, or four-stage, with a temperature gradient, and the highest temperature of the final stage is lower than the boiling point of the eutectic formed by the mixed molten salt. To further catalyze graphitization, the temperature can be raised to 550-750℃ after low-temperature carbonization and before high-temperature carbonization for further heat treatment. At this high-temperature stage, the residual Al / Sn components are reduced to Al-Sn alloy phase, which catalyzes the graphitization of carbon layers, thereby better volatilizing the alloy template effect to support the formation of extended carbon structures.

[0058] In step (V), the minimum temperature for high-temperature carbonization is higher than the boiling point of the eutectic formed by the mixed molten salt. Under high-temperature carbonization, the soft biomass material is carbonized into hard carbon material, and urea and phosphoric acid are converted into nitrogen and phosphorus and incorporated into the hard carbon material. High-temperature carbonization involves raising the temperature to 1100-1400℃ at a rate of 3-8℃ / min and holding it for 1-5 hours. At this carbonization temperature, AlCl3 and SnCl2 volatilize and form uniform pores in the hard carbon material. KCl partially volatilizes, and the remainder is converted into soluble potassium salts and removed by acid washing.

[0059] In step (VI), the weak acid used can be acetic acid. Of course, other weak inorganic or organic acids can also be used besides acetic acid. The solid-liquid ratio of the carbide to the weak acid is 1:15~25 g / mL. For example, the solid-liquid ratio can be, but is not limited to, 1:15 g / mL, 1:16 g / mL, 1:17 g / mL, 1:18 g / mL, 1:19 g / mL, 1:20 g / mL, 1:21 g / mL, 1:22 g / mL, 1:23 g / mL, 1:24 g / mL, or 1:25 g / mL. The concentration of acetic acid is 0.5~2.0 mol / L. For example, the concentration may be, but is not limited to, 0.5 mol / L, 0.6 mol / L, 0.7 mol / L, 0.8 mol / L, 0.9 mol / L, 1.0 mol / L, 1.2 mol / L, 1.4 mol / L, 1.6 mol / L, 1.8 mol / L, or 2.0 mol / L. The pickling time is 3~15 h. For example, it may be, but is not limited to, 3 h, 4 h, 5 h, 6 h, 7 h, 8 h, 9 h, 10 h, 11 h, 12 h, 13 h, 14 h, or 15 h. The temperature is 60~100℃. For example, it may be, but is not limited to, 60℃, 65℃, 70℃, 75℃, 80℃, 85℃, 90℃, 95℃, or 100℃. The washing process in this step includes washing with water until the pH reaches 6.0±0.2, and drying is vacuum drying at 70~100℃ for 6~20h. For example, the temperature can be, but is not limited to, 70℃, 75℃, 80℃, 85℃, 90℃, 95℃, 100℃, and the time can be, but is not limited to, 6h, 8h, 10h, 12h, 14h, 16h, 18h, 20h.

[0060] To better illustrate the purpose, technical solution, and beneficial effects of this invention, the invention will be further described below with reference to specific embodiments. It should be noted that the methods described below are further explanations of this invention and should not be construed as limiting the invention. The embodiments of this invention include descriptions of the technical solution for biomass hard carbon materials and descriptions of the technical solution for the preparation method of biomass hard carbon materials.

[0061] Example 1 This embodiment describes a method for preparing biomass hard carbon material, which includes the following steps.

[0062] (I) Weigh 1 kg of sugarcane bagasse, vacuum dry it at 60℃ for 12 h to remove free water, and then air-jet pulverize it until Dv50 is 5~6 μm to obtain the first precursor.

[0063] (II) Prepare a mixture of urea and phosphoric acid (90 wt.%) at a molar ratio of 1:3, then add 5 wt.% H3BO3 to the mixture. Add the first precursor and the mixture to a pressure-resistant reactor at a ratio of 1:15 g / mL. Stir and heat to 160°C for 3 hours, then allow to cool to room temperature. After depressurizing the reactor, put the mixture into a centrifuge and wash it with water until the pH reaches 6.5. Then put it into a vacuum drying oven and dry it at 80°C for 12 hours to obtain the second precursor.

[0064] (III) Anhydrous AlCl3, anhydrous KCl and anhydrous SnCl2 were added to a VC10 mixer in a mass ratio of AlCl3:KCl 6:4 and (AlCl3 and KCl: SnCl2 85:15) and mixed with nitrogen to obtain a mixed molten salt. The second precursor and the mixed molten salt were ball-milled in a mass ratio of 1:1 using a ball mill at a speed of 300 rpm for 4 hours to obtain the third precursor.

[0065] (IV) The third precursor was loaded into a graphite crucible and placed in a high-temperature tube furnace. Under a nitrogen protective atmosphere (flow rate of 1 L / min), two-stage temperature-controlled pre-carbonization was carried out. The first stage heating rate was 5 °C / min, and the temperature was increased to 200 °C and held for 1 h. The second stage heating rate was 1 °C / min, and the temperature was increased to 350 °C and held for 2 h.

[0066] (V) Heat to 1300℃ at a heating rate of 5℃ / min and hold for 2 hours. Then allow to cool naturally to room temperature, and remove the crucible and the material inside.

[0067] (VI) Add the material to a 1 mol / L acetic acid solution at a dosage of 1:20 g / mL, put it into a reaction vessel, stir at 80℃ for 12 h, let it cool naturally, put it into a centrifuge, wash it with water until the pH is 6.0, then put it into a vacuum drying oven and vacuum dry at 80℃ for 12 h, cool it to room temperature, and then break it up and sieve it with a 400 mesh sieve.

[0068] Example 2 This embodiment describes a method for preparing biomass hard carbon material, which includes the following steps.

[0069] (I) Weigh 1 kg of corn cob, vacuum dry it at 60℃ for 12 h to remove free water, and then air-jet pulverize it until Dv50 is 5~6 μm to obtain the first precursor.

[0070] (II) Prepare a mixture of urea and phosphoric acid (90 wt.%) at a molar ratio of 1:3, then add 5 wt.% H3BO3 to the mixture. Add the first precursor and the mixture to a pressure-resistant reactor at a ratio of 1:15 g / mL. Stir and heat to 160°C for 3 hours, then allow to cool to room temperature. After depressurizing the reactor, put the mixture into a centrifuge and wash it with water until the pH reaches 6.5. Then put it into a vacuum drying oven and dry it at 80°C for 12 hours to obtain the second precursor.

[0071] (III) Anhydrous AlCl3, anhydrous KCl and anhydrous SnCl2 were added to a VC10 mixer in a mass ratio of AlCl3:KCl 6:4 and (AlCl3 and KCl: SnCl2 85:15) and mixed with nitrogen to obtain a mixed molten salt. The second precursor and the mixed molten salt were ball-milled in a mass ratio of 1:1 using a ball mill at a speed of 300 rpm for 4 hours to obtain the third precursor.

[0072] (IV) The third precursor was loaded into a graphite crucible and placed in a high-temperature tube furnace. Under a nitrogen protective atmosphere (flow rate of 1 L / min), two-stage temperature-controlled pre-carbonization was carried out. The first stage heating rate was 5 °C / min, and the temperature was increased to 200 °C and held for 1 h. The second stage heating rate was 1 °C / min, and the temperature was increased to 350 °C and held for 2 h.

[0073] (V) Heat to 1300℃ at a heating rate of 5℃ / min and hold for 2 hours. Then allow to cool naturally to room temperature, and remove the crucible and the material inside.

[0074] (VI) Add the material to a 1 mol / L acetic acid solution at a dosage of 1:20 g / mL, put it into a reaction vessel, stir at 80℃ for 12 h, let it cool naturally, put it into a centrifuge, wash it with water until the pH is 6.0, then put it into a vacuum drying oven and vacuum dry at 80℃ for 12 h, cool it to room temperature, and then break it up and sieve it with a 400 mesh sieve.

[0075] Example 3 This embodiment describes a method for preparing biomass hard carbon material, which includes the following steps.

[0076] (I) Weigh 1 kg of sugarcane bagasse, vacuum dry it at 60℃ for 12 h to remove free water, and then air-jet pulverize it until Dv50 is 5~6 μm to obtain the first precursor.

[0077] (II) Prepare a mixture of urea and phosphoric acid (90 wt.%) at a molar ratio of 1:3, then add 5 wt.% H3BO3 to the mixture. Add the first precursor and the mixture to a pressure-resistant reactor at a ratio of 1:15 g / mL. Stir and heat to 160°C for 3 hours, then allow to cool to room temperature. After depressurizing the reactor, put the mixture into a centrifuge and wash it with water until the pH reaches 6.5. Then put it into a vacuum drying oven and dry it at 80°C for 12 hours to obtain the second precursor.

[0078] (III) Anhydrous AlCl3, anhydrous KCl and anhydrous SnCl2 were added to a VC10 mixer in a mass ratio of AlCl3:KCl 6:4 and (AlCl3 and KCl: SnCl2 85:10) and mixed with nitrogen to obtain a mixed molten salt. The second precursor and the mixed molten salt were ball-milled in a mass ratio of 1:1 using a ball mill at a speed of 300 rpm for 4 hours to obtain the third precursor.

[0079] (IV) The third precursor was loaded into a graphite crucible and placed in a high-temperature tube furnace. Under a nitrogen protective atmosphere (flow rate of 1 L / min), two-stage temperature-controlled pre-carbonization was carried out. The first stage heating rate was 5 °C / min, and the temperature was increased to 200 °C and held for 1 h. The second stage heating rate was 1 °C / min, and the temperature was increased to 350 °C and held for 2 h.

[0080] (V) Heat to 1300℃ at a heating rate of 5℃ / min and hold for 2 hours. Then allow to cool naturally to room temperature, and remove the crucible and the material inside.

[0081] (VI) Add the material to a 1 mol / L acetic acid solution at a dosage of 1:20 g / mL, put it into a reaction vessel, stir at 80℃ for 12 h, let it cool naturally, put it into a centrifuge, wash it with water until the pH is 6.0, then put it into a vacuum drying oven and vacuum dry at 80℃ for 12 h, cool it to room temperature, and then break it up and sieve it with a 400 mesh sieve.

[0082] Example 4 This embodiment describes a method for preparing biomass hard carbon material, which includes the following steps.

[0083] (I) Weigh 1 kg of sugarcane bagasse, vacuum dry it at 60℃ for 12 h to remove free water, and then air-jet pulverize it until Dv50 is 5~6 μm to obtain the first precursor.

[0084] (II) Prepare a mixture of urea and phosphoric acid (90 wt.%) at a molar ratio of 1:3, then add 5 wt.% H3BO3 to the mixture. Add the first precursor and the mixture to a pressure-resistant reactor at a ratio of 1:15 g / mL. Stir and heat to 160°C for 2 hours, then allow to cool to room temperature. After depressurizing the reactor, put the mixture into a centrifuge and wash it with water until the pH reaches 6.5. Then put it into a vacuum drying oven and dry it at 80°C for 12 hours to obtain the second precursor.

[0085] (III) Anhydrous AlCl3, anhydrous KCl and anhydrous SnCl2 were added to a VC10 mixer in a mass ratio of AlCl3:KCl 6:4 and (AlCl3 and KCl: SnCl2 85:15) and mixed with nitrogen to obtain a mixed molten salt. The second precursor and the mixed molten salt were ball-milled in a mass ratio of 1:1 using a ball mill at a speed of 300 rpm for 4 hours to obtain the third precursor.

[0086] (IV) The third precursor was loaded into a graphite crucible and placed in a high-temperature tube furnace. Under a nitrogen protective atmosphere (flow rate of 1 L / min), two-stage temperature-controlled pre-carbonization was carried out. The first stage heating rate was 5 °C / min, and the temperature was increased to 200 °C and held for 1 h. The second stage heating rate was 1 °C / min, and the temperature was increased to 350 °C and held for 2 h.

[0087] (V) Heat to 1300℃ at a heating rate of 5℃ / min and hold for 2 hours. Then allow to cool naturally to room temperature, and remove the crucible and the material inside.

[0088] (VI) Add the material to a 1 mol / L acetic acid solution at a dosage of 1:20 g / mL, put it into a reaction vessel, stir at 80℃ for 12 h, let it cool naturally, put it into a centrifuge, wash it with water until the pH is 6.0, then put it into a vacuum drying oven and vacuum dry at 80℃ for 12 h, cool it to room temperature, and then break it up and sieve it with a 400 mesh sieve.

[0089] Example 5 This embodiment describes a method for preparing biomass hard carbon material, which includes the following steps.

[0090] (I) Weigh 1 kg of sugarcane bagasse, vacuum dry it at 60℃ for 12 h to remove free water, and then air-jet pulverize it until Dv50 is 5~6 μm to obtain the first precursor.

[0091] (II) Prepare a mixture of urea and phosphoric acid (90 wt.%) at a molar ratio of 1:3, then add 5 wt.% H3BO3 to the mixture. Add the first precursor and the mixture to a pressure-resistant reactor at a ratio of 1:15 g / mL. Stir and heat to 160°C for 4 hours, then allow to cool to room temperature. After depressurizing the reactor, put the mixture into a centrifuge and wash it with water until the pH reaches 6.5. Then put it into a vacuum drying oven and dry it at 80°C for 12 hours to obtain the second precursor.

[0092] (III) Anhydrous AlCl3, anhydrous KCl and anhydrous SnCl2 were added to a VC10 mixer in a mass ratio of AlCl3:KCl 6:4 and (AlCl3 and KCl: SnCl2 85:15) and mixed with nitrogen to obtain a mixed molten salt. The second precursor and the mixed molten salt were ball-milled in a mass ratio of 1:1 using a ball mill at a speed of 300 rpm for 4 hours to obtain the third precursor.

[0093] (IV) The third precursor was loaded into a graphite crucible and placed in a high-temperature tube furnace. Under a nitrogen protective atmosphere (flow rate of 1 L / min), two-stage temperature-controlled pre-carbonization was carried out. The first stage heating rate was 5 °C / min, and the temperature was increased to 200 °C and held for 1 h. The second stage heating rate was 1 °C / min, and the temperature was increased to 350 °C and held for 2 h.

[0094] (V) Heat to 1300℃ at a heating rate of 5℃ / min and hold for 2 hours. Then allow to cool naturally to room temperature, and remove the crucible and the material inside.

[0095] (VI) Add the material to a 1 mol / L acetic acid solution at a dosage of 1:20 g / mL, put it into a reaction vessel, stir at 80℃ for 12 h, let it cool naturally, put it into a centrifuge, wash it with water until the pH is 6.0, then put it into a vacuum drying oven and vacuum dry at 80℃ for 12 h, cool it to room temperature, and then break it up and sieve it with a 400 mesh sieve.

[0096] Example 6 This embodiment describes a method for preparing biomass hard carbon material, which includes the following steps.

[0097] (I) Weigh 1 kg of sugarcane bagasse, vacuum dry it at 70℃ for 15 h to remove free water, and then air-jet pulverize it until Dv50 is 3~5 μm to obtain the first precursor.

[0098] (II) Prepare a mixture of urea and phosphoric acid (90 wt.%) at a molar ratio of 1:3, then add 5 wt.% H3BO3 to the mixture. Add the first precursor and the mixture to a pressure-resistant reactor at a ratio of 1:20 g / mL. Stir and heat to 120°C for 5 hours, then allow to cool to room temperature. After depressurizing the reactor, put the mixture into a centrifuge and wash it with water until the pH reaches 6.5. Then put it into a vacuum drying oven and dry it at 100°C for 18 hours to obtain the second precursor.

[0099] (III) Anhydrous AlCl3, anhydrous KCl and anhydrous SnCl2 were added to a VC10 mixer in a mass ratio of AlCl3:KCl 6:4 and (AlCl3 and KCl: SnCl2 85:15) and mixed with nitrogen to obtain a mixed molten salt. The second precursor and the mixed molten salt were ball-milled in a mass ratio of 1:2 using a ball mill at a speed of 250 rpm for 8 hours to obtain the third precursor.

[0100] (IV) The third precursor was loaded into a graphite crucible and placed in a high-temperature tube furnace. Under a nitrogen protective atmosphere (flow rate of 1 L / min), two-stage temperature-controlled pre-carbonization was carried out. The first stage heating rate was 5 °C / min, and the temperature was increased to 200 °C and held for 1 h. The second stage heating rate was 1 °C / min, and the temperature was increased to 350 °C and held for 2 h.

[0101] (V) Heat to 1200℃ at a heating rate of 8℃ / min and hold for 4 hours. Then allow to cool naturally to room temperature, and remove the crucible and the material inside.

[0102] (VI) Add the material to a 2.0 mol / L acetic acid solution at a dosage of 1:20 g / mL, put it into a reaction vessel, stir at 80℃ for 12 h, let it cool naturally, put it into a centrifuge, wash it with water until the pH is 6.0, then put it into a vacuum drying oven and vacuum dry at 80℃ for 12 h, cool it to room temperature, and then break it up and sieve it with a 400 mesh sieve.

[0103] Example 7 This embodiment describes a method for preparing biomass hard carbon material, which includes the following steps.

[0104] (I) Weigh 1 kg of sugarcane bagasse, vacuum dry it at 60℃ for 12 h to remove free water, and then air-jet pulverize it until Dv50 is 5~6 μm to obtain the first precursor.

[0105] (II) Prepare a mixture of urea and phosphoric acid (concentration of phosphoric acid is 88 wt.%) at a molar ratio of 1:5, then add 8 wt.% H3BO3 to the mixture. Add the first precursor and the mixture to a pressure-resistant reactor at a ratio of 1:15 g / mL. Stir and heat to 160℃ for 3 hours, then allow to cool to room temperature. After depressurizing the reactor, put the mixture into a centrifuge and wash it with water until the pH reaches 6.5. Then put it into a vacuum drying oven and dry it at 90℃ for 10 hours to obtain the second precursor.

[0106] (III) Anhydrous AlCl3, anhydrous KCl and anhydrous SnCl2 were added to a VC10 mixer at a mass ratio of AlCl3:KCl 1:1 and (AlCl3 and KCl: SnCl2 80:20) and mixed with nitrogen to obtain a mixed molten salt. The second precursor and the mixed molten salt were ball-milled at a mass ratio of 1:2 using a ball mill at a speed of 400 rpm for 4 hours to obtain the third precursor.

[0107] (IV) The third precursor was loaded into a graphite crucible and placed in a high-temperature tube furnace. Under an argon protective atmosphere (flow rate of 5 L / min), two-stage temperature-controlled pre-carbonization was carried out. The first stage heating rate was 10 °C / min, and the temperature was increased to 230 °C and held for 2.0 h. The second stage heating rate was 3.0 °C / min, and the temperature was increased to 380 °C and held for 4 h.

[0108] (V) Heat to 1300℃ at a heating rate of 5℃ / min and hold for 2 hours. Then allow to cool naturally to room temperature, and remove the crucible and the material inside.

[0109] (VI) Add the material to a 1.5 mol / L acetic acid solution at a dosage of 1:20 g / mL, put it into a reaction vessel, stir at 100℃ for 5 h, let it cool naturally, put it into a centrifuge, wash it with water until the pH is 6.1, then put it into a vacuum drying oven and vacuum dry at 100℃ for 8 h, cool it to room temperature, and then break it up and sieve it with a 400 mesh sieve.

[0110] Example 8 This embodiment describes a method for preparing biomass hard carbon material, which includes the following steps.

[0111] (I) Weigh 1 kg of sugarcane bagasse, vacuum dry it at 60℃ for 12 h to remove free water, and then air-jet pulverize it until Dv50 is 5~6 μm to obtain the first precursor.

[0112] (II) Prepare a mixture of urea and phosphoric acid (90 wt.%) at a molar ratio of 1:3. Add the first precursor and the mixture to a pressure-resistant reactor at a ratio of 1:15 g / mL. Stir and heat to 160°C for 3 hours and then allow to cool to room temperature. After depressurizing the reactor, put the mixture into a centrifuge and wash it with water until the pH reaches 6.5. Then put it into a vacuum drying oven and dry it at 80°C for 12 hours to obtain the second precursor.

[0113] (III) Anhydrous AlCl3, anhydrous KCl and anhydrous SnCl2 were added to a VC10 mixer in a mass ratio of AlCl3:KCl 6:4 and (AlCl3 and KCl: SnCl2 85:15) and mixed with nitrogen to obtain a mixed molten salt. The second precursor and the mixed molten salt were ball-milled in a mass ratio of 1:1 using a ball mill at a speed of 300 rpm for 4 hours to obtain the third precursor.

[0114] (IV) The third precursor was loaded into a graphite crucible and placed in a high-temperature tube furnace. Under a nitrogen protective atmosphere (flow rate of 1 L / min), two-stage temperature-controlled pre-carbonization was carried out. The first stage heating rate was 5 °C / min, and the temperature was increased to 200 °C and held for 1 h. The second stage heating rate was 1 °C / min, and the temperature was increased to 350 °C and held for 2 h.

[0115] (V) Heat to 1300℃ at a heating rate of 5℃ / min and hold for 2 hours. Then allow to cool naturally to room temperature, and remove the crucible and the material inside.

[0116] (VI) Add the material to a 1 mol / L acetic acid solution at a dosage of 1:20 g / mL, put it into a reaction vessel, stir at 80℃ for 12 h, let it cool naturally, put it into a centrifuge, wash it with water until the pH is 6.0, then put it into a vacuum drying oven and vacuum dry at 80℃ for 12 h, cool it to room temperature, and then break it up and sieve it with a 400 mesh sieve.

[0117] Example 9 This embodiment describes a method for preparing biomass hard carbon material, which includes the following steps.

[0118] (I) Weigh 1 kg of sugarcane bagasse, vacuum dry it at 60℃ for 12 h to remove free water, and then air-jet pulverize it until Dv50 is 5~6 μm to obtain the first precursor.

[0119] (II) Prepare a mixture of urea and phosphoric acid (90 wt.%) at a molar ratio of 1:3, then add 5 wt.% H3BO3 to the mixture. Add the first precursor and the mixture to a pressure-resistant reactor at a ratio of 1:15 g / mL. Stir and heat to 160°C for 3 hours, then allow to cool to room temperature. After depressurizing the reactor, put the mixture into a centrifuge and wash it with water until the pH reaches 6.5. Then put it into a vacuum drying oven and dry it at 80°C for 12 hours to obtain the second precursor.

[0120] (III) Anhydrous AlCl3, anhydrous KCl and anhydrous SnCl2 were added to a VC10 mixer in a mass ratio of AlCl3:KCl 6:4 and (AlCl3 and KCl: SnCl2 85:15) and mixed with nitrogen to obtain a mixed molten salt. The second precursor and the mixed molten salt were ball-milled in a mass ratio of 1:1 using a ball mill at a speed of 300 rpm for 4 hours to obtain the third precursor.

[0121] (IV) The third precursor was loaded into a graphite crucible and placed in a high-temperature tube furnace for pre-carbonization under a nitrogen protective atmosphere (flow rate of 1 L / min). The temperature was increased to 350 °C at a heating rate of 2 °C / min and held for 1 h to obtain the fourth precursor.

[0122] (V) Heat to 1300℃ at a heating rate of 5℃ / min and hold for 2 hours. Then allow to cool naturally to room temperature, and remove the crucible and the material inside.

[0123] (VI) Add the material to a 1 mol / L acetic acid solution at a dosage of 1:20 g / mL, put it into a reaction vessel, stir at 80℃ for 12 h, let it cool naturally, put it into a centrifuge, wash it with water until the pH is 6.0, then put it into a vacuum drying oven and vacuum dry at 80℃ for 12 h, cool it to room temperature, and then break it up and sieve it with a 400 mesh sieve.

[0124] Comparative Example 1 This comparative example illustrates a method for preparing a biomass hard carbon material, comprising the following steps.

[0125] (I) Weigh 1 kg of sugarcane bagasse, vacuum dry it at 60℃ for 12 h to remove free water, and then air-jet pulverize it until Dv50 is 5~6 μm to obtain the first precursor.

[0126] (II) Prepare a mixture of urea and phosphoric acid (90 wt.%) at a molar ratio of 1:3, then add 5 wt.% H3BO3 to the mixture. Add the first precursor and the mixture to a pressure-resistant reactor at a ratio of 1:15 g / mL. Stir and heat to 160°C for 3 hours, then allow to cool to room temperature. After depressurizing the reactor, put the mixture into a centrifuge and wash it with water until the pH reaches 6.5. Then put it into a vacuum drying oven and dry it at 80°C for 12 hours to obtain the second precursor.

[0127] (III) Anhydrous AlCl3 and anhydrous KCl were added to a VC10 mixer at a mass ratio of 6:4 and mixed with nitrogen to obtain a mixed molten salt. The second precursor and the mixed molten salt were ball-milled at a mass ratio of 1:1 using a ball mill at a speed of 300 rpm for 4 hours to obtain the third precursor.

[0128] (IV) The third precursor was loaded into a graphite crucible and placed in a high-temperature tube furnace. Under a nitrogen protective atmosphere (flow rate of 1 L / min), two-stage temperature-controlled pre-carbonization was carried out. The first stage heating rate was 5 °C / min, and the temperature was increased to 200 °C and held for 1 h. The second stage heating rate was 1 °C / min, and the temperature was increased to 350 °C and held for 2 h.

[0129] (V) Heat to 1300℃ at a heating rate of 5℃ / min and hold for 2 hours. Then allow to cool naturally to room temperature, and remove the crucible and the material inside.

[0130] (VI) Add the material to a 1 mol / L acetic acid solution at a dosage of 1:20 g / mL, put it into a reaction vessel, stir at 80℃ for 12 h, let it cool naturally, put it into a centrifuge, wash it with water until the pH is 6.0, then put it into a vacuum drying oven and vacuum dry at 80℃ for 12 h, cool it to room temperature, and then break it up and sieve it with a 400 mesh sieve.

[0131] Comparative Example 2 This comparative example illustrates a method for preparing a biomass hard carbon material, comprising the following steps.

[0132] (I) Weigh 1 kg of sugarcane bagasse, vacuum dry it at 60℃ for 12 h to remove free water, and then air-jet pulverize it until Dv50 is 5~6 μm to obtain the first precursor.

[0133] (II) Anhydrous AlCl3, anhydrous KCl and anhydrous SnCl2 were added to a VC10 mixer in a mass ratio of AlCl3:KCl 6:4 and (AlCl3 and KCl: SnCl2 85:15) and mixed with nitrogen to obtain a mixed molten salt. The first precursor and the mixed molten salt were ball-milled in a mass ratio of 1:1 using a ball mill at a speed of 300 rpm for 4 hours to obtain the second precursor.

[0134] (III) The second precursor was loaded into a graphite crucible and placed in a high-temperature tube furnace. Under a nitrogen protective atmosphere (flow rate of 1 L / min), two-stage temperature-controlled pre-carbonization was carried out. The first stage heating rate was 5 °C / min, and the temperature was increased to 200 °C and held for 1 h. The second stage heating rate was 1 °C / min, and the temperature was increased to 350 °C and held for 2 h.

[0135] (IV) Heat to 1300℃ at a heating rate of 5℃ / min and hold for 2 hours. Then allow to cool naturally to room temperature, and remove the crucible and the material inside.

[0136] (V) Add the material to a 1mol / L acetic acid solution at a dosage of 1:20g / mL, put it into a reaction vessel, stir at 80℃ for 12h, let it cool naturally, put it into a centrifuge, wash it with water until the pH is 6.0, then put it into a vacuum drying oven and vacuum dry at 80℃ for 12h. After cooling to room temperature, it is then broken up and sieved with a 400 mesh sieve.

[0137] Comparative Example 3 This comparative example illustrates a method for preparing a biomass hard carbon material, comprising the following steps.

[0138] (I) Weigh 1 kg of sugarcane bagasse, vacuum dry it at 60℃ for 12 h to remove free water, and then air-jet pulverize it until Dv50 is 5~6 μm to obtain the first precursor.

[0139] (II) Prepare a mixture of urea and phosphoric acid (90 wt.%) at a molar ratio of 1:3, then add 5 wt.% H3BO3 to the mixture. Add the first precursor and the mixture to a pressure-resistant reactor at a ratio of 1:15 g / mL. Stir and heat to 160°C for 3 hours, then allow to cool to room temperature. After depressurizing the reactor, put the mixture into a centrifuge and wash it with water until the pH reaches 6.5. Then put it into a vacuum drying oven and dry it at 80°C for 12 hours to obtain the second precursor.

[0140] (III) Anhydrous ZnCl2, anhydrous KCl and anhydrous SnCl2 were added to a VC10 mixer in a mass ratio of ZnCl2:KCl of 6:4 and (ZnCl2 and KCl: SnCl2 of 85:15) and mixed with nitrogen to obtain a mixed molten salt. The second precursor and the mixed molten salt were ball-milled in a mass ratio of 1:1 using a ball mill at a speed of 300 rpm for 4 hours to obtain the third precursor.

[0141] (IV) The third precursor was loaded into a graphite crucible and placed in a high-temperature tube furnace. Under a nitrogen protective atmosphere (flow rate of 1 L / min), two-stage temperature-controlled pre-carbonization was carried out. The first stage heating rate was 5 °C / min, and the temperature was increased to 200 °C and held for 1 h. The second stage heating rate was 1 °C / min, and the temperature was increased to 350 °C and held for 2 h.

[0142] (V) Heat to 1300℃ at a heating rate of 5℃ / min and hold for 2 hours. Then allow to cool naturally to room temperature, and remove the crucible and the material inside.

[0143] (VI) Add the material to a 1 mol / L acetic acid solution at a dosage of 1:20 g / mL, put it into a reaction vessel, stir at 80℃ for 12 h, let it cool naturally, put it into a centrifuge, wash it with water until the pH is 6.0, then put it into a vacuum drying oven and vacuum dry at 80℃ for 12 h, cool it to room temperature, and then break it up and sieve it with a 400 mesh sieve.

[0144] Comparative Example 4 This comparative example illustrates a method for preparing a biomass hard carbon material, comprising the following steps.

[0145] (I) Weigh 1 kg of sugarcane bagasse, vacuum dry it at 60℃ for 12 h to remove free water, and then air-jet pulverize it until Dv50 is 5~6 μm to obtain the first precursor.

[0146] (II) Prepare a mixture of urea and phosphoric acid (90 wt.%) at a molar ratio of 1:3, then add 5 wt.% H3BO3 to the mixture. Add the first precursor and the mixture to a pressure-resistant reactor at a ratio of 1:15 g / mL. Stir and heat to 160°C for 3 hours, then allow to cool to room temperature. After depressurizing the reactor, put the mixture into a centrifuge and wash it with water until the pH reaches 6.5. Then put it into a vacuum drying oven and dry it at 80°C for 12 hours to obtain the second precursor.

[0147] (III) Anhydrous AlCl3, anhydrous KCl and anhydrous SnCl2 were added to a VC10 mixer in a mass ratio of AlCl3:KCl 6:4 and (AlCl3 and KCl: SnCl2 85:15) and mixed with nitrogen to obtain a mixed molten salt. The second precursor and the mixed molten salt were ball-milled in a mass ratio of 1:1 using a ball mill at a speed of 300 rpm for 4 hours to obtain the third precursor.

[0148] (IV) The third precursor was loaded into a graphite crucible and placed in a high-temperature tube furnace. The temperature was increased to 1300°C at a rate of 5°C / min and held for 2 hours. Then the temperature was allowed to cool naturally to room temperature. The crucible and the material inside were then removed.

[0149] (V) Add the material to a 1mol / L acetic acid solution at a dosage of 1:20g / mL, put it into a reaction vessel, stir at 80℃ for 12h, let it cool naturally, put it into a centrifuge, wash it with water until the pH is 6.0, then put it into a vacuum drying oven and vacuum dry at 80℃ for 12h. After cooling to room temperature, it is then broken up and sieved with a 400 mesh sieve.

[0150] Comparative Example 5 This comparative example illustrates a method for preparing a biomass hard carbon material, comprising the following steps.

[0151] (I) Weigh 1 kg of coconut shell, vacuum dry at 60℃ for 12 h to remove free water, and then air-jet pulverize until Dv50 is 5~6 μm to obtain the first precursor.

[0152] (II) Prepare a mixture of urea and phosphoric acid (90 wt.%) at a molar ratio of 1:3, then add 5 wt.% H3BO3 to the mixture. Add the first precursor and the mixture to a pressure-resistant reactor at a ratio of 1:15 g / mL. Stir and heat to 160°C for 3 hours, then allow to cool to room temperature. After depressurizing the reactor, put the mixture into a centrifuge and wash it with water until the pH reaches 6.5. Then put it into a vacuum drying oven and dry it at 80°C for 12 hours to obtain the second precursor.

[0153] (III) Anhydrous AlCl3, anhydrous KCl and anhydrous SnCl2 were added to a VC10 mixer in a mass ratio of AlCl3:KCl 6:4 and (AlCl3 and KCl: SnCl2 85:15) and mixed with nitrogen to obtain a mixed molten salt. The second precursor and the mixed molten salt were ball-milled in a mass ratio of 1:1 using a ball mill at a speed of 300 rpm for 4 hours to obtain the third precursor.

[0154] (IV) The third precursor was loaded into a graphite crucible and placed in a high-temperature tube furnace. Under a nitrogen protective atmosphere (flow rate of 1 L / min), two-stage temperature-controlled pre-carbonization was carried out. The first stage heating rate was 5 °C / min, and the temperature was increased to 200 °C and held for 1 h. The second stage heating rate was 1 °C / min, and the temperature was increased to 350 °C and held for 2 h.

[0155] (V) Heat to 1300℃ at a heating rate of 5℃ / min and hold for 2 hours. Then allow to cool naturally to room temperature, and remove the crucible and the material inside.

[0156] (VI) Add the material to a 1 mol / L acetic acid solution at a dosage of 1:20 g / mL, put it into a reaction vessel, stir at 80℃ for 12 h, let it cool naturally, put it into a centrifuge, wash it with water until the pH is 6.0, then put it into a vacuum drying oven and vacuum dry at 80℃ for 12 h, cool it to room temperature, and then break it up and sieve it with a 400 mesh sieve.

[0157] The boiling points Tr of the mixed molten salt and AlCl3 alone in step (III) of Example 1 and Comparative Example 1 were tested respectively, and the results are as follows: Figure 1 As shown. The test conditions for the boiling point Tr were: TG testing was performed using a NETZSCH STA 449 F5 thermometer in an N2 atmosphere (99.999% high-purity nitrogen), with a heating rate of 5℃ / min and a temperature range of 30~500℃. Figure 1 The results show that at 300°C, the mass retention rate of the alloy in Example 1 is as high as 95.1%, while the mass retention rate of the binary system in Comparative Example 1 is 68.0%. Pure AlCl3 has almost completely volatilized at 300°C. Therefore, the mixed molten salt formed by the ternary system of AlCl3, KCl and SnCl2 can significantly suppress the volatilization of AlCl3.

[0158] EPR detection signals were performed on the fourth precursors of Example 1 and Comparative Example 1, respectively, and the results are as follows: Figure 2 As shown. EPR testing method: A Bruker EMXplus spectrometer (configured with an ER 4119HS resonant cavity) was used for testing under the following parameters: microwave frequency 9.85 GHz, microwave power 0.5 mW, modulation amplitude 0.05 mT, and sweep range 335 ± 5 mT. All samples were placed in quartz tubes (sample volume 20 mg) under Ar gas protection. After calibrating the magnetic field with DPPH, the signal peak height (H) at g = 2.002 was recorded. pp This value serves as a characterization of free radical concentration. Each sample group was tested three times, and the average value was taken. Figure 2 The results show that the signal peak height (Hpp) at g=2.002 in Example 1 is only 28% of that in Comparative Example 1, indicating that SnCl2 has reducing properties during low-temperature carbonization and can effectively reduce the ·O2 generated during the pyrolysis of phosphate esters. - The presence of free radicals weakens the EPR detection signal, and the reduced free radical concentration directly inhibits the generation of active defects in the carbon skeleton, reducing irreversible sodium consumption during SEI formation, thus greatly improving the initial coulombic efficiency.

[0159] The degree of substitution (DP) of the phosphate groups in the second precursors of Examples 1-9 and Comparative Examples 1-5 was tested respectively. The physical properties and chemical composition of the biomass hard carbon materials prepared in Examples 1-9 and Comparative Examples 1-5 were then tested, and the results are shown in Table 1. The electrochemical performance of the biomass hard carbon materials prepared in Examples 1-9 and Comparative Examples 1-5 was also tested, and the results are shown in Table 1.

[0160] (1) Physical properties and chemical composition testing The nitrogen and phosphorus atom percentages were obtained by EDS scanning of single and multi-particle elemental distributions, and the nitrogen and phosphorus doping amounts were calculated. Malvern Panaco Empyrean XRD was used to measure the d002 value and the full width at half maximum (FWHM) of the 002 diffraction peak. Raman spectroscopy using Renishaw inVia Reflex was used to measure the ID / IG ratio, with the ID / IG peak at 1350 cm⁻¹. -1 ) and G peak (1580cm) -1 The integral intensity ratio of ).

[0161] (2) Electrochemical performance testing A polyvinylidene fluoride (PVDF) solution with a mass fraction of 6-7% was prepared using N-methylpyrrolidone as a solvent. Biomass hard carbon materials prepared in Examples 1-9 and Comparative Examples 1-5, PVDF, and conductive carbon black were mixed uniformly at a mass ratio of 90:5:5. The mixture was coated onto copper foil and vacuum dried in a vacuum drying oven at 110°C for 4 hours. The resulting material was then punched into small discs with a diameter of 14 mm. These discs were then transferred to an argon-filled glove box and assembled into 2430 coin cells. A three-component mixed solvent of 1 mol / L NaPF6 (EC:DMC:EMC = 1:1:1, volume ratio) was used as the electrolyte. A sodium metal sheet was used as the counter electrode, and a 16 μm thick Ube membrane was used as the separator. The electrochemical performance of the assembled half-cells was tested on an electrochemical detection system at 25°C, with a charge / discharge voltage range of 0 V to 2.0 V and a rate of 0.1 C to obtain the initial coulombic efficiency and initial reversible capacity. Next, a rate test was performed under the following conditions: 0.1C→0.2C→0.5C→1C→2C→5C→0.1C, with each rate cycle repeated 5 times. The voltage range was 0-2.0V, in order to obtain the reversible capacity and capacity retention rate at 5C.

[0162] Table 1. Performance test results of materials in Examples 1-9 and Comparative Examples 1-5

[0163] As shown in Table 1, the biomass hard carbon anode materials prepared in Examples 1-8 have an initial reversible capacity ≥340 mAh / g, with a maximum of 365 mAh / g; an initial charge-discharge coulombic efficiency ≥82.8%, with a maximum of 90.3%; a 5C capacity ≥255 mAh / g, with a maximum of 310 mAh / g; and a 5C capacity retention rate ≥75%, with a maximum of 85%. Specifically, compared to Examples 4 and 5, Example 1 shows that changing the phosphoesterification time alters the degree of substitution. By controlling the esterification time, the degree of substitution can be adjusted to achieve precise control of the material structure, thereby affecting the electrochemical performance.

[0164] Comparing Example 1 and Comparative Example 1, it is evident that the XRD (002) full width at half maximum (FWHM) of Example 1 decreased from approximately 5.2° to approximately 3.1° after the addition of SnCl2, and its performance in all aspects completely surpassed that of Comparative Example 1, demonstrating the crucial role of SnCl2 in the ternary salt system. Comparing Example 1 and Comparative Example 2, it is clear that Comparative Example 2 lacks the phosphate esterification step, resulting in carbon framework disorder (ID / IG = 1.35), failure of interlayer orientation, and disordered carbon layer stacking, leading to a comprehensive decline in performance. Comparing Example 1 and Comparative Example 3, it is evident that in Comparative Example 3, Zn... 2+ Unable to replace Al 3+ The effect of this is that the overall performance decreases. Comparing Example 1 and Comparative Example 4, it can be seen that direct high-temperature carbonization without pre-carbonization results in a significant decrease in Al performance. 3+ The phosphoric acid cannot coordinate with the phosphate-esterified soft biomass material in time and thus volatilizes, resulting in poor material performance. In Comparative Example 5, hard nutshell biomass was used. The lignin in the hard nutshell encapsulates the cellulose, hindering phosphoric acid permeation and limiting pretreatment. In addition, the dense structure of hard nutshell biomass hinders the diffusion of mixed molten salt, leading to uneven template distribution and disordered carbon layer arrangement, thus resulting in poor material performance.

[0165] Finally, it should be noted that the above embodiments are only used to illustrate the technical solutions of the present invention and are not intended to limit the scope of protection of the present invention. Although the present invention has been described in detail with reference to preferred embodiments, it is not limited to those listed in the embodiments. Those skilled in the art should understand that modifications or equivalent substitutions can be made to the technical solutions of the present invention without departing from the essence and scope of the technical solutions of the present invention.

Claims

1. A method for preparing biomass hard carbon material, characterized in that, Including the following steps: (I) The soft biomass material is dried and pulverized to obtain the first precursor; (II) The precursor is dispersed in a mixture containing urea and phosphoric acid, reacted, washed, and dried to obtain a second precursor; (III) The second precursor and the mixed molten salt are mixed and then ball-milled to obtain the third precursor, wherein the mixed molten salt comprises AlCl3, KCl and SnCl2; (IV) The third precursor is carbonized at low temperature under an inert atmosphere to obtain a fourth precursor, wherein the maximum temperature of the low-temperature carbonization is lower than the boiling point of the eutectic formed by the mixed molten salt. (V) The fourth precursor is subjected to high-temperature carbonization to obtain a carbide, wherein the minimum temperature of the high-temperature carbonization is higher than the boiling point of the eutectic formed by the mixed molten salt; (VI) The carbide is acid-washed with a weak acid and then dried.

2. The method for preparing biomass hard carbon material according to claim 1, characterized in that, Includes at least one of the following features (1) to (18): (1) The soft biomass material is selected from at least one of bamboo shavings, sugarcane bagasse, corn cob and corn stalk; (2) The soft biomass material is vacuum dried to remove free water and then air-jet pulverized to obtain the first precursor. The vacuum drying temperature is 50~75℃ and the time is 5~20h. (3) The Dv50 of the first precursor is 1~10μm; (4) The molar ratio of urea to phosphoric acid is 1:2~5; (5) The concentration of the phosphoric acid is 85 wt.% or higher; (6) Boric acid is also added to the mixture, wherein the boric acid accounts for 3-10 wt.% of the mixture. (7) The reaction temperature is 120~200℃ and the time is 1~6h; (8) The solid-liquid ratio of the first precursor and the mixture is 1:10~20 g / mL; (9) The washing in step (II) is to use a centrifuge to wash with water until the pH is 6.5±0.2, and the drying is to use vacuum drying at 70~100℃ for 6~20h; (10) The weight ratio of AlCl3 to KCl is 1:3 / 7 to 7 / 3, and SnCl2 accounts for 10 to 20% of the sum of the weights of AlCl3 and KCl; (11) The weight ratio of the second precursor to the mixed molten salt is 1:1~2; (12) The ball milling speed is 200~400 rpm and the time is 2~10 h; (13) The inert atmosphere is selected from at least one of argon, nitrogen, helium, neon, krypton and xenon; (14) The boiling point of the eutectic formed by the mixed molten salt is 300~500℃; (15) The high-temperature carbonization includes raising the temperature to 1100-1400℃ at a rate of 3-8℃ / min and holding it for 1-5 hours; (16) The pickling time is 3~15h and the temperature is 60~100℃; (17) The washing in step (VI) includes washing with water until the pH is 6.0±0.2, and the drying is vacuum drying at 70~100℃ for 6~20h; (18) The degree of substitution (DP) of the phosphate group in the second precursor is 0.2 to 0.

4.

3. The method for preparing biomass hard carbon material according to claim 1, characterized in that, The low-temperature carbonization adopts a multi-stage carbonization process, and the highest temperature of the low-temperature carbonization is below 500°C.

4. The method for preparing biomass hard carbon material according to claim 3, characterized in that, The multi-stage carbonization process includes raising the temperature to 200-280℃ at a rate of 1-10℃ / min and holding it for 0.5-3.0h, then raising the temperature to 300-500℃ at a rate of 0.5-5.0℃ / min and holding it for 1-5h.

5. The method for preparing biomass hard carbon material according to claim 1, characterized in that, The weak acid is acetic acid.

6. The method for preparing biomass hard carbon material according to claim 5, characterized in that, The solid-liquid ratio of the carbide and the weak acid is 1:15~25 g / mL, and the concentration of the acetic acid is 0.5~2.0 mol / L.

7. The biomass hard carbon material prepared by the method for preparing biomass hard carbon material according to any one of claims 1 to 6, characterized in that, The d002 range is 0.39~0.42nm, the graphitization degree ID / IG is 0.90~1.10, and the full width at half maximum (FWHM) of the XRD 002 diffraction peak is 3.1±0.4°.

8. The biomass hard carbon material according to claim 7, characterized in that, It is doped with nitrogen and phosphorus, with nitrogen doping amount of 0.8~1.3 wt.% and phosphorus doping amount of 1.0~1.8 wt.%.

9. The application of the biomass hard carbon material according to claim 7 or 8 as a negative electrode material in a sodium-ion battery, characterized in that, Includes at least one of the following features (i) to (iv): (i) 0.1C first reversible capacity ≥335mAh / g; (ii) 0.1C initial charge-discharge coulombic efficiency ≥ 82.8%; (iii) 5C capacity ≥ 255mAh / g; (iv) 5C capacity retention ≥75%.

Citation Information

Patent Citations

  • Hard carbon negative electrode material, preparation method thereof, pole piece containing hard carbon negative electrode material and lithium ion battery

    CN111864206A

  • Hard carbon material, preparation method and application thereof, and sodium ion battery

    CN119461326A